Bakti Sosial sebagai Wujud Pengabdian dan Kepedulian terhadap Lingkungan - Arnoldus Yansen Ane; Merlina Mbari; Maria Vinsensia Atu Leuhoe; Yupriska Budiman; Matilda Pia Bone (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Independent Learning Independent Campus (MBKM Mandiri) activities are mandatory activities for every student of the Faculty of Teacher Training and Education, Widya Mandira Catholic University, Kupang to gain new knowledge and gain factual experience from the place where the field activities are carried out. MBKM activities outside the classroom are carried out through community service. Community service is carried out through social service activities that take place at SMA Negeri 4 Kupang and Pantai Warna Oesapa, Kec. Kelapa Lima, East Nusa Tenggara Province. Social service activities aim to increase the participation of MBKM students and school residents, to be directly involved in social service, and to direct students to be able to create a clean, healthy, and comfortable environment. This community service uses a participatory method of implementation, where this method involves direct collaboration between KKN participants and school residents. The results of this study indicate that the social service activities carried out provide enormous benefits where the school and beach environments become more beautiful, neat, and well-maintained.